Pengaruh Customer Relationship Management (CRM) Terhadap Kepuasan Nasabah Pinjaman Pada PT. Bank Pembangunan Daerah Sumatera Barat Cabang Painan - Romi Susanto (JURNAL PUNDI, 2021)
Fast traslate Icon translate The purpose of this study was to analyze the influence of commitment, communication, and service quality on loan customer satisfaction at PT. Bank Pembangunan Daerah Sumatera Barat Cabang Painan. To achieve customer satisfaction PT. Bank Pembangunan Daerah Sumatera Barat Cabang Painan makes it easy for customers to make loans to personal loans which is one type of credit that is in great demand of the public. This is because the procedure is easier, namely the credit ceiling taken based on multiplying the employee's net salary with the provisions with the bank. The population in this study were all loan customers at PT. PT. Bank Pembangunan Daerah Sumatera Barat Cabang Painan totaling 4,985 people. The sampling technique used was random sampling, while the number of samples used for analysis was 100 people. Data analysis techniques used to test hypotheses are multiple linear regression. The hypothesis testing uses statistical T test. The results of the study show that the commitment variable does not have an influence on the satisfaction of loan customers at PT. Bank Pembangunan Daerah Sumatera Barat Cabang Painan. While communication and service quality variables have a significant influence on loan customer satisfaction at PT. Bank Pembangunan Daerah Sumatera Barat Cabang Painan. Keywords: Commitment, Communication, Service quality, and customer satisfaction